New Pigment ( Khudhory Red Pigment ) to Evaluate Oocytes Viability - Mudhafar Abdulhussein M. Al-khudhory (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Infertility remains a significant global health challenge, affecting approximately 60–80 million couples worldwide. Assisted Reproductive Technologies (ART) are widely employed to address infertility, and assessing oocyte viability is essential for ensuring the success of these techniques. Specific Background: The conventional trypan blue stain is commonly used for oocyte viability assessment, but concerns regarding its synthetic composition and potential cytotoxicity have prompted the search for safer alternatives. Knowledge Gap: Limited research has explored the use of natural pigments for oocyte viability testing, particularly those derived from antioxidant-rich sources like berries. Aims: This study aimed to develop and evaluate a novel natural pigment, named Khudhory Red, extracted from mulberry (Morus rubra), as an eco-friendly and safe alternative to trypan blue. Results: The pigment successfully differentiated viable and non-viable oocytes without causing cytotoxic effects, showing comparable performance to trypan blue in staining selectivity and clarity. Novelty: This is the first documented use of mulberry extract as a natural oocyte viability stain, demonstrating both safety and cost-effectiveness. Implications: The findings suggest Khudhory Red as a sustainable and biocompatible pigment for reproductive biology research, potentially replacing synthetic dyes in oocyte assessment.Highlight : The study successfully prepared a new pigment (Khudhory Red) to evaluate oocyte viability. The new pigment showed no side effects on oocytes and acted similarly to trypan blue. Khudhory Red is natural, organic, safe, cheap, and easily available. Keywords : Infertility, Oocyte, Khudhory Red Pigment, New Pigment, Trypan Blue